Diagnostic Utility of Computed Tomography Perfusion in the Telestroke Setting. Issue 9 (2nd June 2022) - Arora, Kshitij; Gaekwad, Aaron; Evans, James; O'Brien, William; Ang, Timothy; Garcia-Esperon, Carlos; Blair, Christopher; Edwards, Leon S.; Chew, Beng L.A.; Delcourt, Candice; Spratt, Neil J.; Parsons, Mark W.; et al.
Abstract : Background: Definitive diagnosis of acute ischemic stroke is challenging, particularly in telestroke settings. Although the prognostic utility of CT perfusion (CTP) has been questioned, its diagnostic value remains under-appreciated, especially in cases without an easily visible intracranial occlusion. We assessed the diagnostic accuracy of routine CTP in the acute telestroke setting. Methods: Acute and follow-up data collected prospectively from consecutive suspected patients with stroke assessed by a state-wide telestroke service between March 2020 and August 2021 at 12 sites in Australia were analyzed. All patients in the final analysis had been assessed with multimodal CT, including CTP, which was post-processed with automated volumetric software. Diagnostic sensitivity and specificity were calculated for multimodal CT and each individual component (noncontrast CT [NCCT], CT angiogram [CTA], and CTP). Final diagnosis determined by consensus review of follow-up imaging and clinical data was used as the reference standard. Results: During the study period, complete multimodal CT examination was obtained in 831 patients, 457 of whom were diagnosed with stroke. Diagnostic sensitivity for ischemic stroke increased by 19.5 percentage points when CTP was included with NCCT and CTA compared with NCCT and CTA alone (73.1% positive with NCCT+CTA+CTP [95% CI, 68.8–77.1] versus 53.6% positive with NCCT+CTA alone [95% CI, 48.9–58.3], P <0.001). No difference was observed between specificities of NCCT+CTA and NCCT+CTA+CTP (98.7% [95% CI, 98.5–100] versus 98.7% [95% CI, 96.9–99.6], P =0.13). Multimodal CT, including CTP, demonstrated the highest negative predictive value (75.0% [95% CI, 72.1–77.7]). Patients with stroke not evident on CTP had small volume infarcts on follow-up (1.2 mL, interquartile range 0.5–2.7mL). Conclusions: Acquisition of CTP as part of a telestroke imaging protocol permits definitive diagnosis of cerebral ischemia in 1 in 5 patients with normal NCCT and CTA.